Social dimensions of public libraries - D'Alí²s-Moner, Adela; Bailac, Assumpta; Hernández-Sánchez, Hilario (Anuario ThinkEPI, 2015)
Public libraries have been social since their inception (they were created to meet a social need), because of their nature (they exist to serve citizens and the society), their roles and objectives (to inform, to train, and to share, create and socialize knowledge), and the values they promote (liberty, equality, democracy and non-discrimination). The complexities of today´s society, and especially the consequences of the economic crisis that began more than eight years ago, very directly affect the need to consider and recognize, beyond doubt, the social dimension of public libraries. They strengthen social cohesion and inclusion, as well as increase collaboration with other stakeholders. In this context, a team composed of librarians and experts from the third sector has created the Social Library Foundation (in Spanish, Fundación Biblioteca Social, FBS). The main objectives are to highlight the social role of public libraries, empower public libraries to carry out more projects targeting the most vulnerable people, and help the third sector to see public libraries as their allies.